2012
DOI: 10.21829/azm.2012.282839
|View full text |Cite
|
Sign up to set email alerts
|

Enriquecimiento ambiental y su efecto en la exhibición de comportamientos estereotipados en jaguares (Panthera onca) del Parque Zoológico Yaguar Xoo, Oaxaca

Abstract: . 2012. Enriquecimiento ambiental y su efecto en la exhibición de comportamientos estereotipados en jaguares (Panthera onca) del Parque Zoológico "Yaguar Xoo", Oaxaca. Acta Zoológica Mexicana (n. s.), 28(2): 365-377. RESUMEN. El desarrollo de programas de enriquecimiento ambiental para animales en cautiverio promueve el bienestar animal aumentando la actividad física, reduciendo el estrés y, previniendo o reduciendo trastornos como las estereotipias o comportamientos anormales. En el Parque Zoológico Yaguar Xo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
1
6
1
3
Order By: Relevance
“…This fact highlights the need to maintain environmental enrichment implementation systematically, otherwise, the benefits may be lost and the welfare conditions may even be worsened, at least, for some individuals. These findings agree with Castillo-Guevara et al (2012), who found similar results for four captive jaguars.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This fact highlights the need to maintain environmental enrichment implementation systematically, otherwise, the benefits may be lost and the welfare conditions may even be worsened, at least, for some individuals. These findings agree with Castillo-Guevara et al (2012), who found similar results for four captive jaguars.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the results support the hypothesis that the environmental enrichments improved the conditions of the four jaguars, regardless the individual variation of response, as indicated by behavioral changes expressed by all tested jaguars, like a reduction in 'inactivity' and an increase in activity-related behaviors. Considering that there are, to our knowledge, only a few peer-reviewed publications in this area for jaguars in zoos (Charlton 1998, Skibiel et al 2007, Castillo-Guevara et al 2012, Vidal et al 2016, and that a systematic assessment of the environmental enrichment effects is the exception (Mellen & MacPhee 2001), the study reported here also adds to this literature. The jaguars expressed some responses that were common for the four tested individuals.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Sellinger and Ha (2005) found that jaguars increased pacing behavior in response to low-level noise, but not to visitor numbers. Three spices (cinnamon, chilli powder, and cumin) and four enrichment models (toy, food, sound, and scent) have been shown to reduce pacing in jaguars (Skibiel et al, 2007;Castillo-Guevara et al, 2012). Unfortunately, the separate effect of each spice or model was not tested by the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Research on animal welfare and environmental enrichment has been biased toward charismatic species, especially primates [Azevedo et al, ; Goulart et al, ; Melfi, ]. Many other species would, however, greatly benefit from environmental enrichment, as the welfare of animals maintained in controlled conditions is key to reduce stress and its biological costs [Moberg, ], including abnormal behaviors such as stereotypies [Castillo‐Guevara et al, ] and reduced reproductive success [Carlstead and Shepherdson, ].…”
Section: Introductionmentioning
confidence: 99%